(untitled) (Conference Series, 2022)
The aim of this research is to discover the fundamental principle of literal interpretation as it pertains to biblical hermeneutics. Hermeneutics is a discipline that establishes principles or techniques for interpreting the meaning of a particular author’s work. Over time, there have been numerous contradictions in the interpretation of the Bible in the field of hermeneutics. This study specifically focuses on biblical hermeneutics and identifies the principles of literal interpretation. This research employs a descriptive qualitative method, with data analysis conducted using Miles and Huberman’s theory. The study reveals three principles of biblical hermeneutics, namely genre context, historical context, and grammatical context. The principles are useful for interpreting the Bible according to a literal interpretation. Moreover, hermeneutics is essential for Bible interpreters to objectively determine the meaning of a text, given its divine inspiration and significance. Ignoring this guide can lead to flawed theories since hermeneutics is the science of biblical interpretation. Previous studies indicate that having an open and curious mindset assists people in comprehending and following the Scripture.